Mesial temporal sclerosis - Kirmani, Batool F. (Journal of Pediatric Neuroradiology, 2012)
Mesial temporal sclerosis is one of the most common pathologies seen in patients with temporal lobe epilepsy. Complex partial seizures arise from the mesial (deepest) part of the temporal region. This region includes the amygdala and the hippocampus. The etiology of mesial temporal sclerosis is still uncertain and controversial. The most popular mechanism implicated in this pathology involves glutamate, an amino acid whose release results in excessive excitability. This model is documented both in animals and in humans. The other mechanism describes neuronal death from seizure induced gene expression and seizure induced energy metabolism deficits. There are many theories linked to the development of this lesion. It is seen as a rare pathological finding in children less than 10 years of age, but it is not uncommon in adolescence. Clinical studies are suggestive of the occurrence of lesions in children with prolonged febrile seizures. The other etiologies include perinatal ischemic insult, hypoglycemia, intrauterine hypoxia, and status epilepticus resulting in hypoxia and edema in the hippocampus. Magnetic resonance imaging is the modality of choice for the detection of the lesion, which demonstrates scarring in the mesial temporal region. The coronal high-resolution fluid-attenuated inversion recovery is known to be one of the best sequences, since sensitivity is high to detect the hyperintensity and atrophy of the hippocampus. The use of magnetic resonance imaging is crucial for the pre-surgical work up for epilepsy. Specific surgical procedures including anterior temporal lobectomy tailored towards resection of the mesial temporal lesion have a much higher rate of success in intractable epilepsy patients. Seizure freedom is seen in 70–95% of patients undergoing resective surgery as compared with 25% of medically treated cases.
Keywords: Mesial temporal sclerosis; temporal lobe epilepsy; temporal lobectomy; MRI; EEG